Cyanobacterial Toxins and Peptides in Lake Vegoritis, Greece (2021)
Zervou, S.-K.; Moschandreou, K.; Paraskevopoulou,A.; Christophoridis, C.; Grigoriadou, E.; Kaloudis, T.; Triantis, T.M.; Tsiaoussi, V.; Hiskia, A. Cyanobacterial Toxins and Peptides in Lake Vegoritis, Greece. Toxins 2021, 13, 394. https://doi.org/10.3390/toxins13060394